Analisis Proses Kegiatan Manajemen Sarana Prasarana di SMP N 1 Percut Sei Tuan - Pandiangan, Errason; Sinurat, Ester; Simbolon, Krisna Natalin; Manik, Lolona (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This research examines the process of managing educational facilities and infrastructure at SMP Negeri 1 Percut Sei Tuan, which is an important factor in supporting the smooth running of teaching and learning activities. The aim of this study is to assess the extent to which the management of facilities and infrastructure at the school complies with applicable regulations. Data was collected through observation methods, documentation studies, and structured interviews. Research findings reveal that the management of facilities and infrastructure at SMP Negeri 1 Percut Sei Tuan includes the stages of needs planning, utilization, inventory recording, maintenance and asset write-off. The planning stage begins with needs analysis and regular evaluation, while the use of facilities is monitored by a special team that carries out routine data collection and evaluation. Inventory is carried out in an organized and documented manner, both manually and digitally. Maintenance of facilities is carried out routinely by school staff to maintain suitability for use, and disposal of items is carried out according to procedures to reduce workload and prevent waste. In general, the management of facilities and infrastructure at SMP Negeri 1 Percut Sei Tuan runs well and supports the learning process, although there are still several deficiencies in the availability of infrastructure that need to be corrected.